The Vulnerability of SMES in the Economic Crisis - ŢÂU, Nicolae; CREŢOIU, Raluca Ionela (Annals of Spiru Haret University. Economic Series, 2014)
The vulnerability of small and medium enterprises is closely related to their reduced volume of activity and insufficient financial resources available to them. Therefore, these types of organizations are more likely to be the subject of the changes that occur in the market. Although there are available a variety of funding sources, most SMEs in Romania are not able to access existing funds as they are not competitive on the single European market. During the economic crisis, the businesses environment but the economical one as well was not beneficial for the Romanian SMEs due to the financial, structural and fiscal instability, which led to negative results, especially on long term.